Nanostructuring for Nitride Light-Emitting Diodes and Optical Cavities - Li, Kwai Hei (Springer Theses, Recognizing Outstanding Ph.D. Research, 2016)
This book describes the design and fabrication of novel nanostructures in III-nitride material systems. It introduces an inexpensive and ultra-efficient nanopatterning method - nanosphere lithography (NSL) - used to develop diversely functional nanostructures, including clover-shaped photonic crystals, nanorings, and nanolenses. Furthermore, the research findings previously distributed in various international scientific journals and conference papers are brought together and methodically presented in a unified form. The book is of interest to postgraduate students, university researchers, R&D engineers and scientists in the fields of nanoelectronics, optoelectronics and photonics.